No carbon "bet hedging" in pine seedlings under prolonged summer drought and elevated CO2. (11th July 2017) - Bachofen, Christoph; Moser, Barbara; Hoch, Günter; Ghazoul, Jaboury; Wohlgemuth, Thomas
Abstract: More frequent drought episodes are expected to cause higher mortality in isohydric tree species such as pines, because individuals close their stomata early during drought in order to maintain constant needle water potentials. It has been suggested that trees delay the ensuing carbon starvation by actively storing carbon at the expense of growth ("bet hedging"). Because such a strategy is only adaptive in drought‐prone regions, we hypothesise that the degree of carbon "bet hedging" should differ between ecotypes. We repeatedly measured the allocation of biomass, starch and soluble sugars to needles, stem and roots in seedlings of nine populations of Pinus sylvestris and Pinus nigra along a gradient from Central Europe to the Mediterranean. During two consecutive growing seasons, seedlings grown from seed were exposed to factorial combinations of 4 months of drought (D1, D2) and ambient/elevated CO2 (aCO2 /eCO2 ). Drought‐stressed pine seedlings did neither increase starch concentrations, nor change biomass production or experience lower mortality under eCO2 compared to aCO2 . By the end of D2, seedlings from drier origin had accumulated more starch but at the same time also more biomass than seedlings from wetter origin. Surprisingly, seedlings acclimatised to dry conditions after D1 so that mortality dropped to zero and drought effects on needle starch ( P. sylvestris ) and overall starch ( P. nigra ), respectively, disappeared after D2. Synthesis . The absence of a trade‐off between carbon storage (starch) and growth (biomass), and the patterns of mortality observed in seedlings growing under combined drought and eCO2 do not support the theory of carbon "bet hedging" in isohydric Pinus sylvestris and Pinus nigra . Results suggest that reduced growth and acclimatisation minimised seedling mortality in the second year. Acclimatisation might thus enable pine seedlings to resist a moderate increase in summer drought frequency expected in the future. Abstract : The absence of a trade‐off between carbon storage (starch) and growth (biomass), and the patterns of mortality observed in seedlings growing under combined drought and elevated CO2 do not support the theory of carbon "bet hedging" in isohydric P. sylvestris and P. nigra . Reduced growth and acclimatisation minimised mortality in the second year, enabling pine seedlings to resist a moderate increase in summer drought frequency expected in the future.